Pengaruh Umur Perusahaan, Kinerja Lingkungan, Sensitivitas Industri dan Media Sosial terhadap Tanggungjawab Sosial Perusahaan - Silfiani Agustin, Shely; Dwi Astuti, Diana; Haifa, Haifa (JAKUMA : Jurnal Akuntansi dan Manajemen Keuangan, 2024)
ABSTRACT This study aims to determine the partial and simultaneous effect on the variables Company Age, Environmental Performance, Industry and Media Sensitivity on Disclosure of Social Responsibility. The data processing method in this study uses descriptive statistical tests, classic assumption tests, namely: normality test, multicollinearity test, and heteroscedasticity test, multiple linear regression analysis, hypotheses namely: t test and F test, and the coefficient of determination, with the help of the SPSS 25 analysis tool The results showed that the variable company age did not significantly influence the disclosure of corporate social responsibility, while the variables of environmental performance, industry and media sensitivity significantly influenced the disclosure of corporate social responsibility, and simultaneously the variables of company age, environmental performance, industry and media sensitivity significant effect on the disclosure of corporate social responsibility.